Relasi Antara Orang Tua Dan Anak Di Stasi Hati Kudus Sitolubanua Paroki Santo Bonifasius Alasa - Foangeraigo Ziliwu; Paulinus Kanisius Ndoa; Evimawati Harefa (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This study departs from the concern of researchers over the reality of the relationship between parents and children. The main problem raised is the attitude of parents in giving their time to children is very minimal both in the form of mentoring and educating. The purpose of this study was to find out what is meant by the relationship between parents and children and to know the description of the relationship between parents and children at Hati Kudus Sitolubanua Station. The research methodology is qualitative research. This research was conducted at Hati Kudus Sitolubanua Station. Subjects were 20 people, data collection methods were observation, interviews and documentation. Data analysis was carried out through three processes, namely: data reduction, data display, and verification. The results of the study illustrate that the relationship between parents and children at the Hati Kudus Sitolubanua station does not fully have much time to establish relationships. There is still a lack of openness between parents and children. there are still families using authoritarian or power parenting styles that have very excessive control and a lack of parental involvement in children's education, especially in children's learning. Parents are able to explain and invite children to understand that family is the first place to find comfort and happiness filled with good relationships, able to create relationships full of prosperity and harmony in the family.